George Orwell's Political Theory as Reflected in Animal Farm (مجلة ديالى للبحوث الانسانية, 2022)
It is generally known that politics is an important theme of George Orwell's (1903-1950). His literary writing is influenced by different political and social changes of his time. As a political thinker, his novels reveal political and social problems that caused the social and political upheavals of his time. He seeks for a political theory that may enrich the society with ideal thoughts. This research aims at showing the political theory as reflected in Animal Farm . It is divided into three sections. Section one illustrates Animal Farm as a novel. Section two shows Animal Farm as a political allegory and section three explains the political views found in Animal Farm. Finally a conclusion that sums up the findings of this research.